2014
DOI: 10.1073/pnas.1401706111
|View full text |Cite
|
Sign up to set email alerts
|

GTP activator and dNTP substrates of HIV-1 restriction factor SAMHD1 generate a long-lived activated state

Abstract: The HIV-1 restriction factor sterile α-motif/histidine-aspartate domain-containing protein 1 (SAMHD1) is a tetrameric protein that catalyzes the hydrolysis of all dNTPs to the deoxynucleoside and tripolyphosphate, which effectively depletes the dNTP substrates of HIV reverse transcriptase. Here, we establish that SAMHD1 is activated by GTP binding to guanine-specific activator sites (A1) as well as coactivation by substrate dNTP binding to a distinct set of nonspecific activator sites (A2). Combined activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
187
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(211 citation statements)
references
References 31 publications
21
187
0
1
Order By: Relevance
“…The reaction profiles were fitted to a sigmoidal kinetic function, which resulted in various degrees of sigmoidal shaped curves expected from cooperativity effect due to allosteric binding. The dGTP reaction showed the lowest cooperativity, which is consistent with that observed previously (27). In contrast, the dCTP reaction profile showed the most pronounced sigmoidal behavior of activation.…”
Section: Gtp Together With Any Of the Four Dntps Induces The Formatiosupporting
confidence: 91%
See 4 more Smart Citations
“…The reaction profiles were fitted to a sigmoidal kinetic function, which resulted in various degrees of sigmoidal shaped curves expected from cooperativity effect due to allosteric binding. The dGTP reaction showed the lowest cooperativity, which is consistent with that observed previously (27). In contrast, the dCTP reaction profile showed the most pronounced sigmoidal behavior of activation.…”
Section: Gtp Together With Any Of the Four Dntps Induces The Formatiosupporting
confidence: 91%
“…Our study provides a structural basis and complementary analysis to the reported study on dGTP/dUTP catalysis by SAMHD1 (27). During the preparation of this manuscript, Hansen et al (27) reported the combined activation of SAMHD1 tetramer by GTP and dUTP.…”
Section: Different Allosteric Dntp Cofactors Activate Samhd1 To a Simsupporting
confidence: 58%
See 3 more Smart Citations